2023
DOI: 10.3390/w15112030
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Bioactive Compounds Extracted from the Egyptian Untapped Green Alga Rhizoclonium hieroglyphicum

Abstract: Finding alternative powerful antibacterial drugs of natural origins is, today, a crucial prerequisite due to the resistance of some bacterial strains to commercial and widely-used medications. Algae are characterized by their bioactive constituents and have a wide spectrum of biotechnological aspects, particularly antibacterial implications. During this study, four concentrations (5, 10, 20, and 40 mg mL–1) of the Egyptian untapped green microalga Rhizoclonium hieroglyphicum (Chlorophyta) were prepared using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Greenway and Dyke [ 58 ] and Elshobary et al [ 12 ] suggested that linoleic acid probably inhibited growth by increasing the permeability of the bacterial membrane as a result of its surfactant action. Linoleic acid was also stated as a model compound of unsaturated fatty acids that selectively inhibited the FabI enzyme and therefore could stop fatty acid production in bacterial membranes [ 59 ]. All nine major components have documented biological activities or medical benefits, including immune-enhancing, antitumor, anticancer, antioxidant, antimicrobial, and anti-inflammatory effects, as mentioned in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Greenway and Dyke [ 58 ] and Elshobary et al [ 12 ] suggested that linoleic acid probably inhibited growth by increasing the permeability of the bacterial membrane as a result of its surfactant action. Linoleic acid was also stated as a model compound of unsaturated fatty acids that selectively inhibited the FabI enzyme and therefore could stop fatty acid production in bacterial membranes [ 59 ]. All nine major components have documented biological activities or medical benefits, including immune-enhancing, antitumor, anticancer, antioxidant, antimicrobial, and anti-inflammatory effects, as mentioned in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…(Chlorophyta) are widely distributed worldwide (Leal et al, 2020), and most Rhizoclonium strains are found in freshwater environments, with a few species that can tolerate medium-to-high salinity conditions (Saber et al, 2017). These algae have been described as an important source of bioactive molecules (Osuna-Ruiz et al, 2019), and have exhibited antibacterial activity compared to standard antibiotics (Morsi et al, 2023). However, the ability of Rhizoclonium spp.…”
Section: Introductionmentioning
confidence: 99%
“…were characterized and identified for the antioxidant and anticancer effects [16] . The ethanolic extract of Rhizoclonium hieroglyphicum had the strongest antibacterial effects and uncovered 30 different bioactive constituents, mainly including long-chain polyunsaturated and saturated fatty acids such as myristic (C14:0), palmitic (C16:0), stearic (C18:0), α-linolenic (C18:3; ω-3), and oleic (C18:1, ω-9) acids, which synergistically make this potent antibacterial action [17] . As a consequence of this, researchers are increasingly looking into new functional uses for the lipids that microalgae store but are unrelated to the creation of bioenergy.…”
Section: Introductionmentioning
confidence: 99%